2021
DOI: 10.47836/pjssh.29.s1.08
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of a Client’s Satisfaction between Online and Face-to-face Counselling in a School Setting

Abstract: During the current Covid-19 pandemic, the social relationship between humans has changed. As noticed, lockdowns and social distancing have become new norms. Unavoidably, counselling services were also affected with social distancing rules, especially in the school setting. Thus, online counselling or e-counselling has begun to gain in popularity, allowing counsellors to offer their services in an alternative way. In order to evaluate the suitability of e-counselling during the current pandemic, a client’s sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Although VSC for K-12 students appears rigorous, its advantages of accessibility and convenience cannot be understated. This finding is corroborated by previous studies (Zainudin et al, 2021). Some researchers such as Mtemeri et al (2021) cited similar advantages but suggested that video counseling is preferred over other VSC methods such as messaging or phone calling.…”
Section: Discussionsupporting
confidence: 84%
“…Although VSC for K-12 students appears rigorous, its advantages of accessibility and convenience cannot be understated. This finding is corroborated by previous studies (Zainudin et al, 2021). Some researchers such as Mtemeri et al (2021) cited similar advantages but suggested that video counseling is preferred over other VSC methods such as messaging or phone calling.…”
Section: Discussionsupporting
confidence: 84%
“…Hence, it is necessary to understand their perspective on relational aspects, not only in the traditional context but also in the emerging context of online therapy. The literature indicates that online therapy seems to be better accepted by clients than by therapists (Watts et al, 2020); clients not only score the working alliance more positively than therapists but also show higher satisfaction levels similar to face-to-face therapy (Zainudin & Yusop, 2018; Zainudin et al, 2021). Regarding clients’ attitudes, previous experience or the knowledge of this possibility seems to lead to more positive attitudes toward online therapy (Knechtel & Erickson, 2021).…”
Section: Clients’ Perspectivementioning
confidence: 99%
“…E-mail is the most frequently used method of e-counseling then and now (Mejah et al, 2019). Presently, additional technologically-advanced modalities such as telephone counseling, private chatting, text messaging, and video conferencing have become available to many (Zainudin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%